2017
DOI: 10.3389/fncel.2017.00096
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182 Regulates Neurite Outgrowth Involving the PTEN/AKT Pathway

Abstract: MicroRNAs are implicated in neuronal development and maturation. Neuronal maturation, including axon outgrowth and dendrite tree formation, is regulated by complex mechanisms and related to several neurodevelopmental disorders. We demonstrated that one neuron-enriched microRNA, microRNA-182 (miR-182), played a significant role in regulating neuronal axon outgrowth and dendrite tree formation. Overexpression of miR-182 promoted axon outgrowth and complexity of the dendrite tree while also increasing the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“… 32 A study in cortical neurons showed that miR-182-5p regulates neurite outgrowth via activation of the PI3K-Akt pathway. 33 Our results also show increased activation of the PI3K-Akt pathway after increase of miR-182-5p and miR-183-5p in PMNs, and a similar trend could be observed in NC siRNA-transfected cultures treated with GDNF. The importance of PI3K-Akt signaling was underlined by Akt inhibition in MPP + -treated cultures, diminishing the beneficial effects of both miRNAs and GDNF on DA neuron survival in PMN cultures.…”
Section: Discussionsupporting
confidence: 86%
“… 32 A study in cortical neurons showed that miR-182-5p regulates neurite outgrowth via activation of the PI3K-Akt pathway. 33 Our results also show increased activation of the PI3K-Akt pathway after increase of miR-182-5p and miR-183-5p in PMNs, and a similar trend could be observed in NC siRNA-transfected cultures treated with GDNF. The importance of PI3K-Akt signaling was underlined by Akt inhibition in MPP + -treated cultures, diminishing the beneficial effects of both miRNAs and GDNF on DA neuron survival in PMN cultures.…”
Section: Discussionsupporting
confidence: 86%
“…Which factor might be the direct target gene of miR-182-5p and interacted with the expression of PTEN still need further investigations. Previous study reported that miR-182 could activate AKT by inhibiting PTEN activity to promote axon outgrowth [41]. Another study showed that miR-182-5p down-regulated PTEN expression to protect H9c2 cells from hypoxia-induced apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al indicated that miR-182 could activate the AKT signaling pathway via increasing AKT phosphorylation. 39 Liu et al found that overexpression of miR-182 could promote the chemoresistance of colorectal cancer cells through activation of PI3K/AKT signaling pathway. 40 Cao et al revealed that miR-182 promote the proliferation and invasion of hepatocellular carcinoma cells via activating AKT/FOXO3a pathway.…”
Section: Discussionmentioning
confidence: 99%